2011
DOI: 10.1007/s10875-011-9542-6
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment of Etanercept and MTX Reverses Th1/Th2, Th17/Treg Imbalance in Patients with Rheumatoid Arthritis

Abstract: Etanercept in combination with MTX ameliorates RA activity by normalizing the distribution of Th17 and Treg, and their related cytokines, which may partly explain the mechanism of combined therapy of Etanercept plus MTX in RA treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
96
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(115 citation statements)
references
References 29 publications
15
96
1
3
Order By: Relevance
“…16 In RA patients treated with MTX alone or in combination with etanercept, no significant changes were observed in serum concentration of IL-4 and IL-10. 43 In our study, itolizumab did not have a clear effect on IL-10, as was previously demonstrated in psoriasis patients receiving the antibody as monotherapy. 35 Regarding IL-4, its levels were higher in the group receiving the antibody, and this effect was maintained during the follow up.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…16 In RA patients treated with MTX alone or in combination with etanercept, no significant changes were observed in serum concentration of IL-4 and IL-10. 43 In our study, itolizumab did not have a clear effect on IL-10, as was previously demonstrated in psoriasis patients receiving the antibody as monotherapy. 35 Regarding IL-4, its levels were higher in the group receiving the antibody, and this effect was maintained during the follow up.…”
Section: Discussionsupporting
confidence: 80%
“…16 In RA patients treated with MTX, a significant decrease in IL-6, IFN-g 54 and TNF 54,55 levels has also been seen. The same effect was obtained in the cases of IL-6 and TNF in patients treated with a combination of MTX with either etanercept 43 or abatacept. 56 In the first study, IFN-g levels did not change, 43 while the second combination was able to diminish synovial inflammatory gene expression, including IFN-g. 57 In the present study, we used a mAb targeting CD6, which is expressed mainly on T cells and is related with differentiation, survival and activation of these lymphocytes.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations